Quantitative analysis of Cola nitida (Vent.) Schott & Endl., 1832 (Malvaceae) uses in southern Benin communities - Kpatinnon, Noudossessi Rufin; Gouwakinnou, Nounagnon Gérard; Houehanou, Dèhouégnon Thierry; Glele, Romain Lucas Kakaï; Ganglo, Jean Cossi (Ethnobotany Research and Applications, 2026)
Background: Cola nitida (Vent.) Schott & Endl., 1832 is a highly valued multipurpose species in Benin, where it plays important socio-cultural, medicinal and economic roles. Despite its wide use, quantitative data on how local communities mobilise and prioritise, its various uses remain limited. The aim of this research was to assess the communities' endogenous knowledge of C. nitida. Methods: In this research, an ethnobotanical survey was carried out among 203 people randomly selected from predefined stakeholder groups (herbalist, healers, dignitaries, Fa priests and users) in six municipalities in southern Benin. Data were collected through individual interviews from September to November 2021. The ethnic coverage rate (ECR), ethnobotanical use value (UV), diversity index (DI), and equitability index (EI) and were calculated to assess the knowledge and uses of C. nitida in the communities with Correspondence Analyses (CA) applied as a multivariate approach. Results: The results show that the name Gbanja is the one most commonly used by local people to designate C. nitida (ECR = 75%) in southern Benin. The species is used for food (100%), cultural (95%), medicinal (83%), medicinal and magical (69%), magical and religious (65%), timber and service wood (19%) and firewood (12%) purposes. The ethnobotanical use value is higher for older people (UV = 11.29), people with an endogenous religion (UV = 10.11) and illiterate people (UV = 11.00). The diversity index (DI) varies widely within the socio-demographic profiles considered and the equitability value (EI) tends towards 1 whatever the socio-demographic profile, thus reflecting an equitable distribution of knowledge within the populations surveyed about the use of C. nitida. Conclusions: It is therefore important to define policies to promote the species in order to limit the adverse effects of global change on its availability and ensure its sustainable use in communities. Keywords: Cola nitida, quantitative ethnobotany, use value, local communities, Benin